RE-ENGINEERING OF ADMINISTRATIVE PROCESSES AND THEIR ROLE IN REDUCING WORK PRESSURE (World Economics and Finance Bulletin, 2024)
The current research aims to determine the extent of the impact of applying business process re-engineering and its dimensions (the technological dimension, the human dimension, the organizational dimension), as an independent variable on work pressure and its dimensions (workload, work environment, role conflict) as a dependent variable, to find the effect between them. The research seeks to diagnose and understanding the extent to which the University of Information and Communications Technology manages re-engineering practices and work pressure. The questionnaire was the main tool for collecting data and information, in addition to personal interview procedures. A sample consisting of (188) employees was selected from the research sample community, and the questionnaire suitable for analysis was (134) questionnaires. (54) were excluded due to the lack of validity of the analysis in the university investigated, and the statistical system (SPSS) and (STAT) were used, and a set of conclusions were reached, the most important of which is the existence of a relationship between process re-engineering and work pressures at the university at the macro level, while there was no The organizational dimension has an impact in reducing work pressures in the university under study. The most important recommendations were to work on investing in the relationship between reengineering processes and work pressure by increasing attention to human resources, providing training requirements regarding new operations, and using technology and electronic platforms to help in knowing everything related to employees
Keywords: re-engineering; process engineering; universities